Weatherability of ACQ-D Treated Wood Modified with Nano-SiO2 and Emulsified Wax after One-year Outdoor Exposure - Rui Jiang; Yuan F. Xu; Xue J. Yang; Lei Zhang; Zhen Y. Fan; Xiao Y. Guo; Bin Q. Sun; Li L. Yu (BioResources)
Southern pine samples were vacuum-pressure impregnated with nano-SiO2 with Nano-SiO2 based on different specific surface areas (60, 150, 200, 380m2.g-1) and impregnated with alkaline copper quat type D (ACQ-D) preservatives or ACQ-D preservatives modified with emulsified wax. The treated wood was exposed outdoors for one year. The effects of emulsified wax and different conditions of nano-SiO2 on the color change, wettability, and thermal stability of the treated wood were evaluated by colorimeter, contact angle tester, and thermogravimetry (TG). The results showed that nano-SiO2 modification was helpful to keep the surface color stable for ACQ-D treated wood, while the effect of emulsified wax and the specific area of nano-SiO2 on the color stability was slight. The static contact angles were increased after outdoor exposure with nano-SiO2 and/or emulsified wax because of the reduction of the free hydroxyl groups, especially for nano-SiO2 with smaller specific surface area. The thermal stability of ACQ-D treated wood could be increased to different degrees depending on the type of nano-SiO2 and whether emulsified wax were present in the treated wood, although the emulsified wax only played an auxiliary effect on the thermal stability of the treated wood.